(untitled) (Research, Society and Development, 2022)
In search of a clearer understanding of the inflammatory processes of eosinophilic esophagitis, this study aimed to understand more about all the questions about this subject, that is, going through each step with improvement. The research was based on an integrative literature review of the qualitative method, supported by the following databases: Pubmed, Elsevier, Scielo and Virtual Health Library. Eosinophilic esophagitis is a chronic inflammatory disease caused by infiltration of eosinophils in the esophagus region, whose main trigger is some food allergens such as: egg, soy, milk, peanuts and crustaceans. The main symptoms are food impaction or dysphagia, and more serious inflammatory processes may occur that end up requiring procedures such as esophageal dilation. Treatments can occur by eliminating food allergens that present positive results, with the use of systemic or topical corticosteroids, as well as the use of proton pump inhibitors. Early diagnosis has the main function of reducing the occurrence of severe symptoms and providing a better quality of life for patients.